Advances in Visual Computing Third International Symposium, ISVC 2007, Lake Tahoe, NV, USA, November 26-28, 2007, Proceedings, Part I - Boyle, Richard; Parvin, Bahram; Koracin, Darko; Paragios, Nikos; Tanveer, Syeda-Mahmood; Ju, Tao; Liu, Zicheng; Coquillart, Sabine; Cruz-Neira, Carolina; Möller, Torsten; Malzbender, Tom (Image Processing, Computer Vision, Pattern Recognition, and Graphics, 2007)
It is with great pleasure that we welcome you to the Proceedings of the 3rd - ternational Symposium on Visual Computing (ISVC 2007) held in Lake Tahoe, Nevada/California. ISVC o?ers a common umbrella for the four main areas of visualcomputing including vision,graphics,visualization,andvirtualreality.Its goal is to provide a forum for researchers, scientists, engineers and practitioners throughout the world to present their latest research ?ndings, ideas, devel- ments, and applications in the broader area of visual computing. Thisyear,theprogramconsistedof14oralsessions,1postersession,6special tracks, and 6 keynote presentations. Following a very successful ISVC 2006, the response to the call for papers was almost equally strong; we received over 270 submissions for the main symposium from which we accepted 77 papers for oral presentation and 42 papers for poster presentation. Special track papers were solicited separately through the Organizing and Program Committees of each track. A total of 32 papers were accepted for oral presentation and 5 papers for poster presentation in the special tracks.